Localization of explosion pulses in a closed space in coal mines - Abdrakova, F.Yu.; Tulepov, M.I.; Baiseitov, D.A.; Beksultan, Zh.B.; Chikhradze, M. (Горение и плазмохимия, 2021)
The data on the prospect of using an artificial high pressure water barrier as a method of localizing the explosion impulse in the confined space of tunnels and mines are presented. The explosion impulse and the process of its decay in interaction with water fog have been studied. In the course of field research, an explosion was simulated in the shock installation, and a method for its localization was developed using four water screens (barriers). The water screen was created using a system of ring-shaped water distribution headers with high pressure nozzles installed in a circle. Hexogen was used as an explosive. Experiments on localization of explosions were carried out on the base of the «Grigol Tsulukidze Mining Institute of Georgia» in Tbilisi, Georgia, together with the research group of the Faculty of Chemistry and Chemical Technology of al Farabi Kazakh National University and the Institute of Combustion Problems. The influence of the water barrier on the process of shock wave attenuation at 3 points of overvoltage of the section is established. The test results showed that the average values of the overpressure in the three sections were reduced by 38.8%, 26.67% and 19.2%, respectively. The action of the shock wave occurs according to an exponential function, and all other wave changes along any other trajectory on the plane of h–t change are described by a single time dependence.